The Impact of Monetary Policy on Financial Markets in Small Open Economies: More or Less Effective During the Global Financial Crisis? - Steven Pennings; Arief Ramayandi; Hsiao Chink Tang (Asian Development Bank (ADB), 2011)
This paper estimates the impact of monetary policy on exchange rates and stock markets for eight small open economies: Australia, Canada, the Republic of Korea, New Zealand, the United Kingdom, Indonesia, Malaysia and Thailand. On average across these countries, a one percentage point surprise rise in official interest rates leads to a 1% appreciation of the exchange rate and a 1% fall in stock market indices. The effect on exchange rates is notably weaker in the non-Organization for Economic Cooperation and Development (OECD) countries with a managed float. For the OECD countries, there is no robust evidence of a change in the effect of policy during the global financial crisis. For the non-OECD countries, there is some evidence of a stronger effect of policy on stock markets during the crisis, although further research is needed to investigate whether this is a result of measurement issues.
hdl:11540/2561
Keywords: E44; E52; G14; 330; Monetary policy effectiveness; exchange rate; stock prices; crisis; Asian economies